A novel anti-inflammatory activity of lysozyme: modulation of serum complement activation. Issue 5 (1998) - Ogundele Ogundele, M. O. M. O.
Abstract : Lysozyme is an ubiquitous enzyme found in most biological secretions and leukocytes. This study was aimed at investigating its interaction with other inflammatory mediators on mucosa surfaces, particularly the complement system. Lysozyme has been shown in our present study, to inhibit the haemolytic activity of serum complement in a dose-dependent fashion, when tested within the levels present in normal and inflamed breast-milk samples, and other mucosal secretions. This represents a new antiinflammatory action of lysozym e in relation to the serum complement, and the exact mode of the interaction need further studies.